Pengaruh Uang Saku dan Self-control Terhadap Perilaku Pembelian Impulsif Merchandise K-Pop Pada Kpopers Karawang - Saepudin, Lisnawati; Suherman, Ujang; Pranata, Rengga Madya (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This study aims to determine the effect of pocket money and self-control on impulsive buying behavior of K-Pop merchandise among K-Pop fans in Karawang. A quantitative approach with a descriptive correlational method was applied. A total of 75 respondents were selected using purposive sampling. Data were collected through an online questionnaire and analyzed using multiple linear regression. The results showed that pocket money has a positive and significant effect on impulsive buying behavior, while self-control has no significant effect. Despite most respondents having high self-control, emotional impulses triggered by idol merchandise remained hard to suppress. Simultaneously, pocket money and self-control significantly influence impulsive buying, although with a relatively small contribution. This research suggests the importance of enhancing financial literacy and strengthening self-control to reduce consumptive behavior among popular culture enthusiasts.